(untitled) (Research, Society and Development, 2020)
Myracrodruon urundeuva, popularly known as aroeira, is widely distributed in the Brazilian territory and is considered a polyvalent species due to its diversity of uses, which include applications such as fuel, wood, forage, apiculture, area recovery, and medicinal use, which is extensively practiced by rural populations. This variety of applications can threaten the species conservation due to overexploitation and the usage of inappropriate techniques, which can result in a decline in natural populations. The objective of this work was to verify the current knowledge about the species and its conservation status. For that, a systematic review was carried out following the PRISMA model, with a search for papers published between 2010 and 2020. 333 articles were initially identified, of which 165 were included in the review. The studies are distributed in the biological activity, plant biology and ecology, chemical composition, ethnobotany, and production categories. Most of them concern the evaluation of the species biological activities, with evidence of anti-inflammatory, anti-microbial, anti-oxidant, anti-fungal, anti-viral, insecticide, and neuroprotective effects, among others, corroborating therapeutic applications of the species described in ethnobotanical studies. The aroeira is not officially considered threatened with extinction. Although many authors assert that the excessive exploitation of M. urundeuva is a threat to its conservation, no data were found to support this assumption. Studies that evaluate the population status of the species, the environmental condition of its distribution area, and the volume of its exploitation are required in order to properly assess the species conservation situation and to propose measures for sustainable use.